Efektivitas Program Keluarga Harapan dalam Menanggulangi Kemiskinan : Studi Kasus di Kota Tanjungpinang Kelurahan Sei Jang - Fauziah Sandy; Rintaria Rintaria; Putri Kesuma Ningrum (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze the effectiveness of the Family Hope Program (PKH) in alleviating poverty, with a case study focus on Sei Jang Village, Tanjungpinang City. PKH is a social assistance program initiated by the government to improve the welfare of the poor through conditional cash assistance. The reason the researcher chose this title was to determine the extent to which PKH is effective in reducing poverty, especially since data shows a decline in the number of PKH recipients in Sei Jang Village in 2023. This study uses a qualitative approach with a descriptive method, where data is obtained through in-depth interviews, observation, and documentation studies. To measure the level of effectiveness, the theory from (Makmur, 2015) was used, which states that the elements of effectiveness include accuracy in timing, accuracy in calculation, accuracy in measurement, accuracy in decision making, accuracy in thinking, accuracy in carrying out orders, accuracy in determining goals, and accuracy in targeting. The results of the study show that PKH has had a positive impact on reducing the economic burden on poor families, particularly in meeting the educational and health needs of children. However, the effectiveness of this program is still hampered by several factors, such as delays in fund disbursement, participants' lack of understanding of the program's terms and conditions, and minimal assistance from relevant officials. In addition, another challenge in the form of inaccuracy in targeting beneficiaries also affects the overall achievement of the program. These findings indicate that better management and supervision are urgently needed. This study concludes that although PKH contributes significantly to poverty alleviation, improvements in management and supervision are needed to maximize the program's objectives. The proposed recommendations include increasing the capacity of social workers, improving the beneficiary selection mechanism, and strengthening coordination among stakeholders at the local level.